1985
DOI: 10.1159/000206331
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cyclic Nucleotides (cAMPcGMP) in Phenylhydrazine-Induced Anemia

Abstract: The studies were carried out on male Wistar rats. The animals were divided into two groups: control and experimental. The hematocrit value and reticulocyte count were determined in blood samples collected from control and experimental rats. The experimental rats received subcutaneous injections of phenylhydrazine manufactured by Sigma for the duration of 3 days. On the 5th day blood samples were collected from all the control and experimental animals and determinations of hematocrit and reticulocyte count were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our previous work demonstrated that indomethacin, like aspirin, also totally blocked the bleedinginduced reversion o f hemoglobin proportions toward newborn values in adult rats. This finding prompted us to rule out the possibility that aspirin could acetylate many proteins and thereby could exert pharmacologic actions unrelated to its effect on PG biosynthesis [36], However, on the basis o f the present study it is not possible to offer a specific mechanism o f action for the need o f ongoing PG synthesis in order to achieve the reversion o f Hb propor tions in adult rats, other than the already known general informations that PGs exert their effect locally and many o f the effects o f these compounds are mediated by 3',5'-cyclic AMP (cAMP) [38], Earlier studies have indicated that erythropoietin action is mediated by cAMP [39,40], a concept further strengthened by the observation that the bone marrow cAMP level is significantly elevated in phenylhydrazine-induced anemic rats [41]. It remains to be seen whether concurrent PG synthesis is required to regu late the synthesis o f cAMP and whether such a situation is necessary for the reverse switching process.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that indomethacin, like aspirin, also totally blocked the bleedinginduced reversion o f hemoglobin proportions toward newborn values in adult rats. This finding prompted us to rule out the possibility that aspirin could acetylate many proteins and thereby could exert pharmacologic actions unrelated to its effect on PG biosynthesis [36], However, on the basis o f the present study it is not possible to offer a specific mechanism o f action for the need o f ongoing PG synthesis in order to achieve the reversion o f Hb propor tions in adult rats, other than the already known general informations that PGs exert their effect locally and many o f the effects o f these compounds are mediated by 3',5'-cyclic AMP (cAMP) [38], Earlier studies have indicated that erythropoietin action is mediated by cAMP [39,40], a concept further strengthened by the observation that the bone marrow cAMP level is significantly elevated in phenylhydrazine-induced anemic rats [41]. It remains to be seen whether concurrent PG synthesis is required to regu late the synthesis o f cAMP and whether such a situation is necessary for the reverse switching process.…”
Section: Discussionmentioning
confidence: 99%